Correlation of p53 immunohistochemistry with TP53 mutational status and overall survival in newly diagnosed acute myeloid leukaemia. Issue 4 (7th August 2022) - Fitzpatrick, Megan J; Boiocchi, Leonardo; Fathi, Amir T; Brunner, Andrew M; Hasserjian, Robert P; Nardi, Valentina
Abstract : Aims: TP53‐ mutated acute myeloid leukaemia (AML) is associated with an adverse prognosis and poor response to traditional chemotherapy regimens. Next‐generation sequencing (NGS) is considered the gold standard method to determine TP53‐ mutational status; however, molecular assays are costly and time‐consuming. In contrast, immunohistochemistry (IHC) can be performed within 1 day of biopsy. We sought to determine an optimal threshold of staining with p53 IHC to predict TP53 ‐mutational status. Methods and results: We identified 142 consecutive patients with newly diagnosed AML with concurrent NGS analysis diagnosed between 2019 and 2020. All cases were stained for p53 IHC and images were scored for the percent of strongly stained p53+ cells by a combination of manual counting and image analysis. We then correlated percent positive staining with mutational status and clinical outcomes. We determined that a threshold of ≥7% strongly stained cells by p53 IHC correlated with the presence of a TP53 mutation with a sensitivity of 67%, specificity of 100%, positive predictive value of 100% and negative predictive value of 90%. TP53 mutation and the presence of ≥7% staining by IHC were associated with shorter overall survival by univariate analysis ( P < 0.01). Conclusion: If the limitations of this study are carefully considered, our findings suggest that p53 protein expression as evaluated by IHC could be used to rapidly predict TP53 ‐mutational status with high specificity and assist in risk stratification in newly diagnosed AML. Abstract :